An Ecological Momentary Assessment of College Women's Decisions to Use Protective Behavioral Strategies. Issue 15 (August 2022) - Scaglione, Nichole M.; Turrisi, Rob; Sell, Nichole M.; Mallett, Kimberly A.; Cleveland, Michael J.
Protective behavioral strategies (PBS) have been associated with reduced risk for sexual assault victimization in college women. Sexual assault risk reduction programs have had limited success increasing PBS use, particularly among heavy drinkers, suggesting a need for additional research on the malleable predictors of PBS use. Whereas longitudinal studies show women's decisions to use PBS can be both planned and reactive, little is known about the decision-making processes that affect PBS use on drinking days, when sexual assault risk may be elevated. The current study used ecological momentary assessment to examine variability in the associations between decision-making and PBS use within and across drinking days in first-semester college women. Participants (56 female drinkers) completed a 14-day protocol with three daily measures of intentions and willingness to use PBS, and once-daily diaries of PBS use. Multilevel models examined between-day and within-day effects of intentions and willingness to use PBS with regards to sexual assault PBS (e.g., communicating sexual boundaries) and drinking PBS (e.g., limiting alcohol consumption), respectively. On days when sexual assault PBS willingness increased throughout the day, women tended to use more sexual assault PBS. This association was strongest among women who were typically less willing to use these PBS. Among women who were the least willing to use drinking PBS, their drinking PBS use decreased on days when they reported increased willingness to use them. Decisions to use sexual assault and drinking PBS on drinking days were qualified by women's typical levels of willingness to use the different PBS. This suggests the need for a multi-faceted intervention strategy that targets both typical and event-level risk. Individual-level alcohol and sexual assault risk reduction approaches could be enhanced with event-level PBS messaging and evaluation.